Peran Humas Digital Pada Publik Eksternal Direktorat Jendral Pendidikan Tinggi, Riset dan Teknologi Dalam Memberikan Pelayanan dan Informasi Publik Terinovatif - Derivanti, Azizah Des; Silaban, Angel Stepani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to determine the role of public relations in providing innovative services and information to the external public of the Directorate General of Higher Education, Research and Technology as well as the activities carried out by the Public Relations of the Directorate General of Higher Education as a distributor of information to the public. This research is motivated by the rapid advancement of technology in providing information to the public where with the rapid development of technology and social media, public relations as the executor of information providers uses various platforms and digital channels in providing information or publications to the public. The purpose of this study was to determine the role of public relations at the Directorate General of Higher Education in providing services and disseminating innovative public information. This study uses the concept of Public Relations / digital public relations which discusses the interaction and dissemination and publication of information using digital communication and social media. This research was conducted using a qualitative approach and using the paradigm of positivism, data collection carried out in this study was in-depth interviews and observations. The results of this study that the role of public relations in disseminating information is to use digital channels and social media, namely Instagram, Twitter, website, Tiktok. From the results of this study is that the Public Relations of the Directorate General of Higher Education disseminates information and publications by utilizing social media Instagram, Twitter, websites and other digital channels.